SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN MAKANAN SEHAT MENGGUNAKAN METODE AHP (Analytic Hierarchy Process) - Muhammad Misdram (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
The need for foods that meet the health standards are indispensable. Every person has different nutritional adequacy standards based on weight and height of each. So to take a decision is a veryimportant in determining the decisions that must be taken to choose healthy foods.The Decision making canbe influenced by several aspects, this can affect the speed of decision making by the decision maker whendecision-making must be fast and accurate. And to seek the best decision this study using AHP method(Hierarcy Analytic Process) is a way to calculate the value of the criteria and compared with thecalculation of the likelihood of each decision taken. The objectives decision support system that is expectedto choose healthy foods can be petrified solve the problem in taking the decision to determine the criteria ofhealthy food through calories, carbohydrates, proteins, and fats.